Politisasi Birokrasi Pemerintahan Desa Pada Era Reformasi - Triputro, R Widodo (JKAP (Jurnal Kebijakan dan Administrasi Publik), 2005)
Public bureaucracy holds a strategic position in government implementation as well as to effort of democratization and autonomy in local and village government scope. Professional bureaucracy apparatus intensely support the increase of public service quality, particular yfor social empowerment as the realization of local and village autonomy essence. The concept of bureaucracy neutrality needs to be bought into reality in order to urge a bureaucracy that more oriented to its main function, namely as public service apparatus. Long history oflndonesian bureaucracy reflects the occuring bureaucracy politization by government regime, with the result that all bureaucracys line become an administration tool in performing is authority centralization. As the consequence, service tends to be addressed to government (patron) by neglecting public service function. It includes in village government scope, in which bureaucracy becomes a political machine, meanwlile serves as an effective controlling tool that limits social access to public arena. The outcome of case study conducted in one village of Bantul Regency with data resource was gained from government official and prominent figures both in regency or village government area, reveals that bureaucracy politization in village government nowdays is much stronger than under new orde era. On the pretext of democratization and social empowerment, government (red : regent and his political party) performs a set of bureaucracy politization in village government. With limited village resource condition, politic euphoria, and conflict as the result of election proces of village government bureaucracy apparatus, government intervences village government and its community. The patron-client relation is between the government with village government and its community. It is evidenced that bureaucracy politization of villlage government is re-carried out, among others is the estabilish of "Paguyuban Pamong" with its main agenda is the winning of regent for next period and also the winning one of political party at last general election 2004